Analisis Penetapan Harga Pokok Produksi pada Perusahaan Manufaktur di Provinsi Daerah Istimewa Yogyakarta - Nasution, Dito Aditia Darma; Muda, Iskandar (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
This study aims to analyze and describe how the determination of the cost of production in manufacturing companies in the Special Region of Yogyakarta Province. The method used in this study is a qualitative approach using instruments in the form of questionnaires and interviews as supporters addressed to the owners of several manufacturing companies in the Special Region of Yogyakarta Province. The research sample of 52 manufacturing companies consisting of 33 medium scale companies and 19 large scale companies. The results showed that the company has more than one goal in setting the cost of production. The most important finding is that the main factor affecting the cost of production is cost. It was also found that all of the samples tested believed that changes in the cost of production would not be effective in increasing sales volume. Keywords: Implementation of Pricing; Market Based Pricing; Cost Based Pricing; Product Cost.